Estrategia de gestión de la información para el departamento de gestión de tierras de la compañía equion energía limited soportada en arquitectura empresarial (2017)
Land management has become the main point of debate in all agendas of the political, economic, social and peace sector of the country, and it has been shown that to carry out large infrastructure projects such as exploitation among them of hydrocarbons, it must have robust technological tools that allow to advance all the processes in front of the administration of the lands under the legal and technical scaffolding, allowing to protect the interests of the investors. Land management, being an interdisciplinary activity that uses people, information and technology for its development, must be pushed in such a way that each component is aimed at meeting the strategic objectives of the companies, and it is there, where the business architecture guides the integration of the business areas with the information technologies allowing to maximize the IT for the benefit of the company.